Reproductive Health Care for Women with Spina Bifida - Amie B. Jackson; Pamela K. Mott (The Scientific World Journal)
Women with spina bifida have unique health care concerns and as the life expectancy of this population increases, they are transitioning from adolescence to womanhood and entering their reproductive years with little information about what to expect. Likewise, their health care providers do not have the benefit of evidence-based research that comprehensively addresses the issues these women may face related to reproduction or aging. Few studies have focused on the effects that spina bifida may have on these women's reproductive systems, nor has attention been paid to the effects that possible reproductive endocrine changes may have on their disability. Needless to say, concerns about sexuality, sexual function, and pregnancy are just as important to these women as they are to their able-bodied counterparts.